Respectable radicals : studies in the politics of railway trade unionism - Howell, David (Ashgate, 1999)
Railway workers were a uniformed and respectable section of the British working class. They built their trade unions in the face of employer hostility, and their organisations played a crucial role in the construction of effective labour politics. Respectable Radicals uses rich archival sources to analyse this history through a series of case studies. This penetrating study is essential reading for all academics interested in the history of transport and labour relations and for all railway enthusiasts.